Optimal waist circumference cut-off points for predicting metabolic syndrome among low-income black South African adults - Eyitayo Omolara Owolabi; Daniel Ter Goon; Oladele Vincent Adeniyi; Anthony Idowu Ajayi (BMC Research Notes, 2018)
Abstract Objective Waist circumference has been identified as one of the strongest predictive tool for metabolic syndrome. This study determines the optimal cut-off point of waist circumference for metabolic syndrome among low-income earning South African black population, in Eastern Cape, South Africa. The optimal waist circumference cut-off point was determined through receiver operating characteristics analysis using the maximum Youden index. Results Among men, waist circumference at a cut-off value of 95.25 cm yielded the highest Youden index of 0.773 (sensitivity = 98%, specificity = 79%, area under curve 0.893). For women, waist circumference of 89.45 cm yielded the highest Youden index of 0.339 (sensitivity = 88%, specificity = 46%, area under curve 0.713). The prevalence of metabolic syndrome among men, women and both sexes using the new cut-off points were: 17.8, 20.8 and 17.7%, respectively, compared to; 15.6, 24.8 and 21.8%, using the traditional cut-off values of 94 and 80 cm for men and women, respectively. The traditional waist circumference value slightly under-estimated the prevalence of metabolic syndrome among men and over-estimated among women and the overall population. A specific waist circumference cut-off point for South African blacks is needed for correct identification of the metabolic state of the populace in order to develop appropriate interventions.